2016
DOI: 10.2147/ijn.s115208
|View full text |Cite
|
Sign up to set email alerts
|

Surface biofunctionalized CdS and ZnS quantum dot nanoconjugates for nanomedicine and oncology: to be or not to be nanotoxic?

Abstract: Herein, for the first time, we demonstrated that novel biofunctionalized semiconductor nanomaterials made of Cd-containing fluorescent quantum dot nanoconjugates with the surface capped by an aminopolysaccharide are not biologically safe for clinical applications. Conversely, the ZnS-based nanoconjugates proved to be noncytotoxic, considering all the parameters investigated. The results of in vitro cytotoxicity were remarkably dependent on the chemical composition of quantum dot (CdS or ZnS), the nature of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 55 publications
5
19
0
Order By: Relevance
“…Figure c,d shows the X‐ray photoelectron spectroscopy (XPS) of the core levels of sputtered CdS thin films. The peaks at 414–402 eV binding energy correlate with the core levels of Cd 2+ (3d 5/2 and 3d 3/2 ), while the peaks at 164–160 eV binding energy correlate with the core levels of S 2− (3d 1/2 and 3d 3/2 ), both keep well in agreement with the reported literatures . The obtained CdS thin film is stoichiometric, as the Cd/S atom ratio given by XPS measurement is 1:0.997.…”
Section: Resultssupporting
confidence: 89%
“…Figure c,d shows the X‐ray photoelectron spectroscopy (XPS) of the core levels of sputtered CdS thin films. The peaks at 414–402 eV binding energy correlate with the core levels of Cd 2+ (3d 5/2 and 3d 3/2 ), while the peaks at 164–160 eV binding energy correlate with the core levels of S 2− (3d 1/2 and 3d 3/2 ), both keep well in agreement with the reported literatures . The obtained CdS thin film is stoichiometric, as the Cd/S atom ratio given by XPS measurement is 1:0.997.…”
Section: Resultssupporting
confidence: 89%
“…However, a facile and “green” mild process using aqueous medium for the preparation of AgInS 2 /polymer nanoconjugates with high luminescent properties (i.e., PL quantum yield, QY > 40%) for augmenting bioimaging sensitivity is beyond the scope of the current study and remains a challenge for the future researches. Nonetheless, this is not a restriction, and QDs produced by aqueous processes with lower values of QY (i.e., typically < 5%) have been successfully applied for numerous applications in bioimaging (e.g., confocal microscopy, flow cytometry) [ 16 , 24 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiplexed molecular imaging relying on fluorescent QDs can reveal the tempospatial relationship among molecules by simultaneously staining several tumor biomarkers [ 6 ]. To overcome the obstacles of QDs for biomedical imaging, the physicochemical properties of QDs such as composition, size, shape, and surface characteristics associated with cytotoxicity have been comprehensively investigated [ 6 , 15 , 16 ]. However, despite the intense research in the realm of quantum dots for nanomedicine applications, the large majority of studies are based on Cd-containing semiconductor core (i.e., CdS, CdSe, and CdTe) synthesized using organometallic process at high temperature [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the toxicity of these nanostructures is known, different coating procedures have been investigated in order to reduce their toxicity. For instance, zinc sulfide (ZnS) QDs functionalized with chitosan have shown no toxic effects on human leukocytes, contrary to the highly toxic cadmium sulfide (CdS) QDs that, even coated with biocompatible chitosan, showed to be toxic in a concentration and time-dependent manner [17]. A summary of the pros and cons of the use of NPs in cancer research is shown in Table 1.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%